Global Resilience in the Face of Aggression: An Analysis of Sanctions Pressure on Russia’s Economy - Honcharenko, Olena; Diachenko, Olha (Problemy Ekorozwoju, 2026)
This study examines the unprecedented scale of international sanctions imposed on the Russian Federation, highlighting their critical role as a tool for economic pressure amid intense geopolitical instability. The primary objective was to quantify the intensity and assess the effectiveness of the international community’s sanction policy toward Russia from 2022 to 2025. Employing a multi-faceted methodology, including comparative and statistical analysis, the research utilizes data from the Russia Sanctions Dashboard, Statista Research Department, and the United Nations Human Rights Monitoring Mission in Ukraine. Core findings reveal that after the full-scale invasion of Ukraine, the number of sanctions grew almost tenfold, an unprecedented event in international practice. These measures target a wide array of economic sectors – from finance to technology – and key individuals, driven by Russia’s violations of international law and territorial annexations. Unprecedented military aggression constitutes a profound global crisis multiplier, precipitating a systemic regression across the entire matrix of the UN SDGs. Consequently, the trajectory for realizing the SDGs necessitates an immediate cessation of hostilities, given that the protracted duration of the conflict directly correlates with the deepening of the global economic crisis; this inevitably intensifies global poverty and food insecurity, substantially widening the critical gap between current progress and the requisite outcomes for fulfilling the 2030 Agenda for Sustainable Development. The observed dynamics show a clear strategic shift, solidifying Russia’s position as the primary target of economic isolation, with 2024 focusing on limiting critical technology imports and disrupting sanction hubs. However, their effectiveness was partially hampered by Russia’s adaptive resilience and ability to find alternative export markets. The practical value of this research lies in providing a framework to optimize international sanction policy, enhancing mechanisms to prevent evasion, strengthening global coordination, and implementing new restrictions to diminish Russia’s economic capacity and reinforce international security. Future research should concentrate on refining enforcement control systems and developing new strategies for capping the price and limiting the volume of Russian energy resources.